2004
DOI: 10.1080/10647440500068206
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cervical Intraepithelial Neoplasia in Generally HealthyWomen With Exophytic Vulvar Condyloma Acuminata

Abstract: AIM: To disclose possible association between exophytic vulvar condyloma acuminata and cervical intraepithelial neoplasia in generally healthy, sexually active women. METHODS: This retrospective study included 74 patients (study group) who were referred for laser vaporization therapy of exophytic vulvar condyloma acuminata, and 88 asymptomatic volunteers without evidence of exophytic vulvar condyloma acuminata (control group) who were referred for screening Papanicolaou (Pap) test cervical evaluation including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
3
1
0
1
Order By: Relevance
“…The former is consistent with the reported results in previous studies that show that people with a higher economic status showed lower risk of development of CC [68,69]. Similar results have been widely reported from population studies in low-income group countries [51], but our results revealed that the same phenomenon exists in Japan, a highincome group country. Although there may be possible confounding factors, such as the awareness of HPV risk being lower in prefectures with lower economic status, governments in those prefectures need to put further effort into the prevention of CC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The former is consistent with the reported results in previous studies that show that people with a higher economic status showed lower risk of development of CC [68,69]. Similar results have been widely reported from population studies in low-income group countries [51], but our results revealed that the same phenomenon exists in Japan, a highincome group country. Although there may be possible confounding factors, such as the awareness of HPV risk being lower in prefectures with lower economic status, governments in those prefectures need to put further effort into the prevention of CC.…”
Section: Discussionsupporting
confidence: 93%
“…In the result of negative binomial GLMs, the positive contribution of Chlamydia in females and Gonorrhea in males was observed. The positive associations between the incidence of STDs and that of CC have often been reported in previous studies [47][48][49][50][51][52] as associations between HPV and other STDs, globally. In particular, Chlamydia and Herpes-simplex infections have often been listed as risk factors for HPV infection in a prospective cohort study [43] and a retrospective cross-sectional study [47].…”
Section: Discussionsupporting
confidence: 64%
“…The oncogenic HPVs such as HPV 16 and 18 are related to malignancies of cervix, vagina, vulva and anus. This suggests that multiple infections of HPVs are common as being supported by previous studies that 11.7-32.1% of women with AGWs had abnormal cervical cytology or histology (Handley et al, 1992;Li et al, 2003;Sadan et al, 2005;Milojkovic et al, 2011). However, since the quadrivalent HPV vaccine has been launched, the incidence of AGWs declines dramatically (Korostil et al, 2013).…”
Section: Introductionsupporting
confidence: 59%
“…2 However, since screening could considerably affect the incidence of cervical cancer, studies of precancerous lesions may provide a more exact estimate of the actual association. So far, knowledge on the associations between GWs and cervical precancers has predominantly originated from case-control studies, [3][4][5][6][7][8][9][10] and only rarely from cohort studies. 11 These studies have been limited by small sample sizes, selected groups of women and/or lack of generalisability to the general population.…”
Section: Introductionmentioning
confidence: 99%